Electrospun PGS:PCL Microfibers Align Human Valvular Interstitial Cells and Provide Tunable Scaffold Anisotropy. Issue 6 (22nd January 2014) - Masoumi, Nafiseh; Larson, Benjamin L.; Annabi, Nasim; Kharaziha, Mahshid; Zamanian, Behnam; Shapero, Kayle S.; Cubberley, Alexander T.; Camci‐Unal, Gulden; Manning, Keefe. B.; Mayer, John E.; Khademhosseini, Ali
<x xml:space="preserve">Abstract</x> Tissue engineered heart valves (TEHV) can be useful in the repair of congenital or acquired valvular diseases due to their potential for growth and remodeling. The development of biomimetic scaffolds is a major challenge in heart valve tissue engineering. One of the most important structural characteristics of mature heart valve leaflets is their intrinsic anisotropy, which is derived from the microstructure of aligned collagen fibers in the extracellular matrix (ECM). In the present study, a directional electrospinning technique is used to fabricate fibrous poly(glycerol sebacate):poly(caprolactone) (PGS:PCL) scaffolds containing aligned fibers, which resemble native heart valve leaflet ECM networks. In addition, the anisotropic mechanical characteristics of fabricated scaffolds are tuned by changing the ratio of PGS:PCL to mimic the native heart valve's mechanical properties. Primary human valvular interstitial cells (VICs) attach and align along the anisotropic axes of all PGS:PCL scaffolds with various mechanical properties. The cells are also biochemically active in producing heart‐valve‐associated collagen, vimentin, and smooth muscle actin as determined by gene expression. The fibrous PGS:PCL scaffolds seeded with human VICs mimick the structure and mechanical properties of native valve leaflet tissues and would potentially be suitable for the replacement of heart valves in diverse patient populations.